A Gender Study on the Leisure Time Activities (LTA) Pursued by the Youth. (1st April 2016) - Jaiswal, Neerja; Bahedia, Anushree
Abstract: Time is a quantitative resource as it can be measured easily. Leisure time is one of the aspects of time along with work and rest. Activities engaged in leisure time are pursued for one's own sake. The present study was undertaken to find the gender difference of leisure time activities pursued by the respondents. The research design of the present study was descriptive in nature. The study comprised of 90 male and 90 female respondents. Findings of the study reported that all the male and female respondents ranked social leisure time activity first on the basis of leisure time activities pursued by them. It also revealed that the male and female respondents spent maximum time in pursuing leisure time activities related to "entertainment". The findings will be helpful to the youth of the nation, academicians and community in adopting different leisure time activities.